Role of Trained Innate Immunity Activation by Metabolic Reprogramming in Immune Response Regulation Against Emerging Viral Infections. - salman mahdey , Aliaa (Libyan Journal of Medical and Applied Sciences, 2025)
Trained innate immunity (TII) is a memory-like adaptation of innate immune effectors that is accomplished through metabolic and epigenetic reprogramming of trained immune cells. In contrast to bacterial and fungal infections where the mechanisms of defense have been well studied, its contribution to antiviral defense is still poorly understood. This study focused on the mechanism of metabolic reprogramming that controls the activation of trained innate immunity and improves antiviral responses during emerging viral infections. Human macrophage derived monocytes and murine models were pre-stimulated with betulinic acid (b-glucan) or monophosphoryl lipid A (MPLA) inducing trained immunity followed by testing with vesicular stomatitis virus (VSV). Seahorse assay, LC-MS/MS, histone modifications (ChIP-qPCR), gene expression and cytokine production were analyzed. β-glucan and MPLA priming promoted hemodynamic glycolytic activation and accumulation of fumarate and succinate as well as stimulating histone marks (H3K4me3, H3K27ac). Trained macrophages had a significant increase in IL-6, TNF-a and IFN-v secretion and upregulation of antiviral genes (IFNB1, ISG15). Survival and virus load were shown to be increased in vivo in v-glucan-trained mice after infection. Metabolic reprograms of antiviral TITI through the connection between activation of glycolysis and epigenetic reprogramming and cytokine priming. These results present immunometabolism as a potential target of new generation antiviral drugs and adjuvants for vaccines.